Classification of SMI Based QoS Attributes for Software as a Services - V, Balaji.; A, Manikandan.; A, Janakiram.; R, Vigneshwaran, (IJRDO -Journal of Computer Science Engineering, 2016)
Cloud computing is a model to produce the computing resources such as infrastructure, platform and software over the internet in on-demand requirements. As Cloud computing creates huge opportunities and value in business domains, the usage of cloud is creeping up dayby-day. Services models (IaaS, SaaS, PaaS) of the cloud computing is on fast mounting. In this paper, we have compared and classified the key QoS attributes required for software as a service based on Service Measurement Index framework.